Charge transfer dynamics of adsorbate molecules on metal and semiconductor surfaces relating to fundamental processes in dye-sensitized solar cells - Britton, Andrew James (2013)
The charge transfer dynamics between adsorbate molecules and surfaces are important for a variety of different technologies but especially for dye-sensitized solar cells. The main aim of this thesis was to study charge transfer between organic molecules and surfaces, especially relating to the situation observed in dye sensitized solar cells.